Intervening for sustainable change: Tailoring strategies to align with values and principles of communities - Metz, Allison; Kainz, Kirsten; Boaz, Annette (Frontiers in Health Services, 2023)
This paper presents a rationale for tailoring implementation strategies within a values-driven implementation approach. Values-driven implementation seeks to organize implementers around clarifying statements of their shared values in ways that harmonize implementation dynamics related to individual and group mental models, relationships among implementers, and the implementation climate. The proposed approach to tailoring strategies is informed by systems theory and emphasizes the need to focus on both tangible events and behaviors, as well deeper patterns, structures, relationships, and mental models, in order to increase the likelihood of sustaining implementation efforts and improving outcomes for people and communities. We offer for consideration three specific sets of context determinants that are under-represented in the implementation literature and that emerge as especially relevant within a systems approach to identifying and successfully tailoring implementation strategies in the implementation setting including relationships, mental models, and implementation climate.